A „Keleti kérdés” és egy régi harcostárs távozása: Ghyczy Kálmán lemondása a házelnökségről 1879-ben - Szigeti, István (Közép-Európai Közlemények, 2023)
In this study, one of Tisza Kálmán’s close collaborators and longtime co-leader of the Left Center Party, Kálmán Ghyczy, talks about the background of his resignation from the presidency and his withdrawal from the frontline of political life, the relationship between the two politicians, and the immediate antecedents of the decision: the Eastern question, i.e. the occupation of Bosnia and Herzegovina we will talk about his political judgment. Kálmán Ghyczy (1808-1888) is a somewhat forgotten, but definitely relegated to the background, figure in Hungarian historiography, although he had a 20-year acquaintance with party leader Kálmán Tisza, then multiple prime ministers, and in fact, between 1865 and 1874, they jointly led the Balközép Party, of which Ghyczy was president, a prestigious he was an orator and politician, and Tisza was his actual organizer and political leader. And between 1875 and 1879, at Tisza’s request, Ghyczy assisted the legislative work of Kálmán Tisza’s first government as Speaker of the House. Our study aims to answer what could have led to the end of this essentially 15-year-long political and working relationship, what prompted Kálmán Ghyczy to end the joint work in 1879 and retire to private life.